FINANCIAL EFFECT OF VARIABLE RETURN ON INITIAL AND RETURN 15 DAYS AFTER AN INITIAL PUBLIC OFFERING IN MANUFACTURING COMPANY IN THE BEJ - Suparyanti, Suparyanti; Nursasmita, Ak., Drs. H. Irfan (Accounting, 2009)
This research was conducted on manufacturing companies in initial public offering period 1997 to 2002. The samples were done by purposive sampling and the period obtained 19 samples. The purpose of this study was to find out what is the influence of financial variables on the initial returns and return 15 days after the IPO. Data collection methods using secondary data through the methods of documentation and literature. The data needed is historical data taken through Capital Market Directory, the JSX Statistics, and Databases MM UII. Initial Return is used to determine the return on the day of the first companies to do IPOs in the secondary market. Analysis of the data used Normality Test, Test of Classical Assumptions, multiple regression. Financial variables used to determine the effect of initial returns and returns 15 days. Results of research conducted there is the influence of financial variables on the initial returns and return 15 days after the IPO. But there was no statistically significant effect between the current ratio, earnings per share and the rate of return on assets. Previous research also no significant effect. This may occur due to micro factors such as differences in capital structure, and macro factors such as economic conditions, politics and culture that can not be controlled. Keywords: Return